Influence of polled direction on the stress distribution in piezoelectric materials - Ilhan, Nihat; Koc, Nagihan (TECHNO-PRESS, 2015)
In this paper, the influence of the polled direction of piezoelectric materials on the stress distribution is studied under time-harmonic dynamical load (time-harmonic Lamb's problem). The system considered in this study consists of piezoelectric covering layer and piezoelectric half-plane, and the harmonic dynamical load acts on the free face of the covering layer. The investigations are carried out by utilizing the exact equations of motion and relations of the linear theory of electro-elasticity. The plane-strain state is considered. It is assumed that the perfect contact conditions between the covering layer and half-plane are satisfied. The boundary value problems under consideration are solved by employing Fourier exponential transformation techniques with respect to coordinates directed along the interface line. Numerical results on the influence of the polled direction of the piezoelectric materials such as PZT-5A, PZT-5H, PZT-4 and PZT-7A on the normal stresses, shear stresses and electric potential acting on the interface plane are presented and discussed. As a result of the analyses, it is established that the polled directions of the piezoelectric materials play an important role on the values of the studied stresses and electric potential.
Keywords: piezoelectric layered material; polled direction; time-harmonic dynamical loading; stress distribution; resonance behavior; HALF-SPACE; COVERING LAYER; PLANE; FIELD; SYSTEM; SLAB; DYNAMICS; CONTACT; Engineering